Penological developments in contemporary China: Populist punitiveness vs. penal professionalism - Li, Enshen (International journal of law, crime and justice, 2017)
This article examines the penal development in China over the last six decades to understand the ways in which populist punitiveness functions in the Chinese political and social contexts. It argues that populist punitiveness in China is a ‘top-down' process whereby manipulative political elites play on public anxieties and fears of crime and social insecurity to serve different political objectives of the Chinese Communist Party. While public sentiment was promoted and reflected in penal policy in revolutionary (1950s-1970s) and reform (1970s-1990s) China, their influence, in the post-reform era (2000s-), has been blocked or filtered by the political will due to the emergence of a series of moderate political agendas. A new penal politics that favors professional knowledge over public opinion to serve the country's soft governance strategy is now taking shape in contemporary penal regime to prevail China's policy-making power and process.